Assessment of Vascular Network Connectivity of Hepatocellular Carcinoma Using Graph-Based Approach - Liu, Qiaoyu; Zhang, Boyu; Wang, Luna; Zheng, Rencheng; Qiang, Jinwei; Wang, He; Yan, Fuhua; Li, Ruokun (Frontiers in Oncology, 2021)
Background: The angiogenesis of liver cancer is a key condition for its growth, invasion, and metastasis. This study aims to investigate vascular network connectivity of hepatocellular carcinoma (HCC) using graph-based approach. Methods: Orthotopic HCC xenograft model (n=10), and the healthy controls (n=10) were established. After 21 days of modeling, hepatic vascular casting and Micro-CT scanning were performed for angiography, followed by blood vessels automatic segmentation and vascular network modeling. The topologic parameters of vascular network, including clustering coefficient (CC), network structure entropy (NSE), and average path length (APL), were quantified. Topologic parameters of the tumor as well as background liver were compared between HCC group and control group. Results: Compared with normal control group, HCC group showed significantly decreased CC [(0.0460±0.01) vs. (0.0520±0.01), p=0.026], and NSE [(0.9894±0.00) vs. (0.9927±0.00), p＜0.001), and increased APL [(0.4334±0.14) vs. 0.1884±0.05, p＜0.001). Compared with normal control group, the background liver of HCC group showed significantly decreased CC [(0.0472±0.00) vs. (0.0520±0.01), p=0.041] and increased NSE [0.9938 (0.9936~0.9940) vs. (0.9927±0.00), p=0.035]. No significant difference was identified for APL between the two groups. Conclusion: Graph-based approach allows quantification of vascular connectivity of HCC. Disrupted vascular topological connectivity exists in HCC as well as the background liver.